Exposure to famine in early life and self-rated health status among Chinese adults: a cross-sectional study from the Chinese Health and Retirement Longitudinal Study (CHARLS) - Wenjie Sun; Wei Li; Sandra Kiplagat; Olatokunbo Osibogun; Ning Sun; Anthony J Kondracki; Mohammad Ebrahimi Kalan; Rime Jebai; Zhen Wei (BMJ Open)
Objective China’s Great Famine between 1959 and 1961 has contributed to numerous adverse health outcomes in Chinese. This study aimed to examine the association between exposure to famine in early life and self-rated health (SRH) in adulthood.Methods 4418 Chinese adults from the 2011 China Health and Retirement Longitudinal Study were included in the analysis. Multivariable logistic regression was conducted to estimate adjusted ORs (aORs) and 95% CIs of the association between exposure to famine in early life and SRH, stratified by sex.Results Participants exposed to famine during infancy were more likely to report poor SRH (aOR 1.33; 95% CI 1.04 to 1.70) compared with the non-exposed group, adjusting for confounders. Males were 32% less likely than females to report poor SRH (aOR 0.68; 95% CI 0.54 to 0.86). Participants diagnosed with chronic diseases (aOR 3.11; 95% CI 2.68 to 3.61), disability (aOR 1.82; 95% CI 1.38 to 2.38) and vision impairment (aOR 2.07; 95% CI 1.72 to 2.49) were more likely to report poor SRH. Participants who were current alcohol users and with abnormal weight were less likely to report poor SRH. Stratification by sex showed no significant association between famine and SRH among males, but a consistently significant association was observed among females (aOR 1.46; 95% CI 1.02 to 2.12).Conclusions Findings from this study indicated that females exposed to famine in China during infancy were more likely to report poor SRH in their adulthood. Implementing interventions to those who were exposed to famine in early life, especially for females, may improve their long-term consequences.